Indonesian primitive art - Hersey, Irwin (The Asia collection, 1991)
Although the great stone monuments of Indonesia, Thailand, Cambodia, and Burma have long been regarded as among the world's great cultural treasures, comparatively little attention has been paid to the art created by the tribal peoples of South-East Asia. This book traces the history of Indonesian primitive art from its origins in the Dong-son culture of northern Vietnam to the present day, revealing how a shared conception of life, death, and the universe has shaped the art of the various tribal groups spread throughout the Indonesian archipelago. Presenting a vast array of work, from textiles and jewelery, to sculptures in wood and stone, this book provides an excellent introduction to this long-neglected wealth of art.